Evaluation of the regenerative potential of 25% doxycycline-loaded biodegradable membrane vs biodegradable membrane alone in the treatment of human periodontal infrabony defects: A clinical and radiological study - Chaturvedi Rashi; Gill Amarjit; Sikri Poonam (Wolters Kluwer Medknow Publications, 2008)
Background: Microbial colonization of the barrier membranes used for guided tissue regeneration is inevitable and can lead to delayed healing. Aims: Antimicrobial coating of the membrane with 25% doxycycline paste has been attempted to prevent infection and achieve enhanced regeneration in periodontal infrabony defects. Materials and Methods: Twenty-four patients with 2-walled or 3-walled infrabony defects were selected and randomly divided into two equal groups. Infrabony defects of group A were treated with a biodegradable membrane coated with 25% doxycycline while those of group B were treated with membrane alone. Clinical assessment of probing depth and attachment level and radiographic evaluation of the defect depth was done preoperatively and at 12 and 24 weeks postoperatively. Statistical Analysis: The relative efficacy of the two treatment modalities were evaluated using the paired Student′s t- test and the comparative evaluation between the two groups was done using the independent Student′s t -test. Results: Both the groups exhibited a highly significant reduction in probing depth and gain in clinical attachment level and linear bone fill at the end of 24 weeks. Comparative evaluation between the two study groups revealed a significant reduction in probing depth ( P = 0.016 FNx01 ) and linear bone fill ( P = 0.02 FNx01 ) in group A as compared to group B. Mean gain in attachment level was greater for group A than for group B but the difference was statistically nonsignificant ( P = 0.065 NS ). Conclusions: The results suggest that doxycycline is beneficial in reducing membrane-associated infection and can potentiate regeneration through host modulation.